Computed Tomography Versus Dacryocystography for the Evaluation of the Nasolacrimal Duct—A Study With 72 Patients. Issue 4 (17th July 2019) - Papathanassiou, Serafim; Koch, Thomas; Suhling, Marie Charlot; Lenarz, Thomas; Durisin, Martin; Stolle, Stefan R. O.; Raab, Peter
Abstract : Objectives: In patients with epiphora, imaging of the nasolacrimal duct is essential not only for differential diagnosis, but also for preoperative planning. Advances in imaging technology and introduction of cone beam computed tomography (CB‐CT) enable the combination of contrast agent‐based imaging with a three dimensional tomography with low radiation exposure. However, the value of CT/CB‐CT as an alternative to conventional dynamic dacryocystography (DCG) has not been evaluated yet. Study Design: Retrospective study. Methods: Conventional DCG was performed preoperatively in 72 consecutive patients treated for epiphora between 01/2013 and 04/2015 in our department. CB‐CT or conventional CT was performed afterward with the contrast media still in place. Three separate experts (two radiologists and one otorhinolaryngologist) analyzed the radiographic images without any information about the respective clinical or surgical findings. The presence of further findings in the CT/CB‐CT (eg, septal deviation, sinusitis) that were not detected in DCG and the overall visibility of the lacrimal duct system in both modalities were evaluated. Results: Good delineations of bone, soft tissue, and contrast agent in the lacrimal system were achieved with both methods. No side effects were noted. Beside the pathology of the lacrimal duct, CT/CB‐CT scans enabled the additional diagnosis of pathologies in the nose and the sinus system in 65.7% of the patients. Accordance in the identified level of obstruction between the two modalities was achieved in 71.4% of the patients. Conclusion: Thus, CT/CB‐CT should be used in conjunction with contrast agent to reliably identify the level of obstruction as preoperative standard and can be used as diagnostic tool in addition to or even instead of conventional DCG. Level of Evidence: 4